Factors influencing compliance with iron supplementation among pregnant women in the city of Muntinlupa - Ordenes, Maria Ana C. (2003)
Poor compliance with iron supplementation has been reported to be one of the causes to the continuing increase in prevalence of iron deficiency anemia among pregnant women. The study was conducted to determine the possible influences of selected factors on the compliance of pregnant women with iron supplementation. A cohort of 105 pregnant women from the City of Muntinlupa were followed up for three months of supplementation. Compliance with the intervention was measured through self-reporting of the number of iron capsules missed to have taken and by pill counting. From these two compliance indicators, the study showed that 54% of the participants were good compliers. After 3 months of iron intervention, the prevalence of iron deficiency anemia slightly decreased to 19% from the initial prevalence of 21%. Although no significant change in the mean hemoglobin level was observed, a number of anemic participants adjudged as good compliers explained a significant increase in hemoglobin. Compliance with iron supplementation, however, was not significantly correlated with change in hemoglobin level, which may have been due to the initial iron status of the participants and other factors not covered in the present study. Educational attainment (p = .003) and the number of instructions received by the pregnant women on iron supplementation (p=.050) were found to be significantly associated with the participants' compliance index.